Slc45a2 and V‐ATPase are regulators of melanosomal pH homeostasis in zebrafish, providing a mechanism for human pigment evolution and disease. (20th December 2012) - Dooley, Christopher M.; Schwarz, Heinz; Mueller, Kaspar P.; Mongera, Alessandro; Konantz, Martina; Neuhauss, Stephan C. F.; Nüsslein‐Volhard, Christiane; Geisler, Robert
Summary: We present here the positional cloning of the Danio rerio albino mutant and show that the affected gene encodes Slc45a2. The human orthologous gene has previously been shown to be involved in human skin color variation, and mutations therein have been implicated in the disease OCA4. Through ultrastructural analysis of the melanosomes in albino alleles as well as the tyrosinase‐deficient mutant sandy, we add new insights into the role of Slc45a2 in the production of melanin. To gain further understanding of the role of Slc45a2 and its possible interactions with other proteins involved in melanization, we further analyzed the role of the V‐ATPase as a melanosomal acidifier. We show that it is possible to rescue the melanization potential of the albino melanosomes through genetic and chemical inhibition of V‐ATPase, thereby increasing internal melanosome pH.